18[F] FDG-PET/CT is a useful molecular marker in evaluating thymoma aggressiveness. - Ahmad Saad, Fathinul Fikri; Nordin, Abdul Jalil; Mohtarrudin, Norhafizah; Hemalata,; Lau, W. F. Eddie (Elsevier, 2011)
A 54 year-old-man presented with chest fullness and difficulty of breathing for 3 months. CT thorax revealed a heterogeneously enhancing mediastinal mass for which CT-guided biopsy results were initially inconclusive. The patient underwent 18F-FDG-PET/CT study for further metabolic characterisation and staging of the disease. 18F-FDG -PET/CT showed heterogeneous FDG-avid mediastinal mass with adjoining multiple FDG-avid hilar lymph nodes, pulmonary and bone metastasis. Final diagnosis of malignant thymoma was confirmed after a successful PET/CT-guided needle biopsy.